Homogenization of the Signorini boundary-value problem in a thick plane junction - Kazmerchuk, Yu.A.; Mel’nyk, T.A. (Нелінійні коливання, 2009)
We consider a mixed boundary-value problem for the Poisson equation in a plane thick junction Ωε which
is the union of a domain Ω₀ and a large number of ε-periodically situated thin rods. The nonuniform
Signorini conditions are given on the vertical sides of the thin rods. The asymptotic analysis of this problem
is made as ε → 0, i.e., when the number of the thin rods infinitely increases and their thickness tends to
zero. With the help of the integral identity method we prove the convergence theorem and show that the
nonuniform Signorini conditions are transformed (as ε → 0) in the limiting variational inequalities in the
region that is filled up with the thin rods when passing to the limit. Existence and uniqueness of the solution
to this non-standard limit problem is established. The convergence of the energy integrals is proved as well. Розглядається мiшана крайова задача для рiвняння Пуассона у плоскому густому з’єднаннi Ωε,
яке є об’єднанням деякої областi Ω₀ та великої кiлькостi ε-перiодично розмiщених тонких
стержнiв. На бiчних сторонах тонких стержнiв задано неоднорiднi крайовi умови Сiньорiнi.
Проведено асимптотичне дослiдження даної задачi при ε → 0, тобто коли кiлькiсть тонких
стержнiв необмежено зростає, а їхня товщина прямує до нуля. З допомогою методу спецiальних iнтегральних тотожностей доведено теорему збiжностi i показано, що неоднорiднi крайовi умови Сiньорiнi трансформуються при ε → 0 у варiацiйнi нерiвностi в областi, яка заповнюється тонкими стержнями у граничному переходi. Доведено iснування та єдинiсть розв’язку
такої нестандартної граничної задачi. Також доведено збiжнiсть iнтегралiв енергiї вихiдної задачi.